Exosomes from activated hepatic stellate cells contain GLUT1 and PKM2: a role for exosomes in metabolic switch of liver nonparenchymal cells. Issue 7 (10th April 2019) - Wan, Lu; Xia, Tian; Du, Yanqin; Liu, Jie; Xie, Yuyu; Zhang, Yijie; Guan, Fei; Wu, Jun; Wang, Xiaochuan; Shi, Chunwei
ABSTRACT: The mechanism of exosomes derived from activated hepatic stellate cells (HSCs) involved in liver fibrosis is poorly understood. We previously reported that hypoxia‐inducible factor 1 (Hif‐1) regulated HSC activation, and, therefore, we investigated in current work whether Hif‐1 regulates exosome secretion and the metabolic switch of HSCs, thus affecting the metabolism of liver nonparenchymal cells. In this study, the characteristics of exosomes from HSCs were assessed via electron microscopy, Western blot analysis, and acetylcholinesterase activity. Confocal microscopy was used to measure the uptake of exosomes by quiescent HSCs, Kupffer cells (KCs), and liver sinusoidal endothelial cells (LSECs). Hif‐1α was inhibited via 2‐ME or specific small interfering RNAs to investigate its role in exosomes derived from HSCs. It was determined that glucose transporter 1 and pyruvate kinase M2 were increasingly expressed in fibrotic liver samples, cell lysates, and exosomes derived from activated HSCs. Exosomes released from HSCs were associated with activation and glucose uptake of HSCs. Delivery of exosomes from activated HSCs induced glycolysis of quiescent HSCs, KCs, and LSECs. Disruption of Hif‐1 expression suppressed the glycolysis effect delivered by exosomes. Conclusively, our results demonstrated that exosomes secreted by activated HSCs affect the metabolic switch of liver nonparenchymal cells via delivery of glycolysis‐related proteins. These findings represent a novel mechanism that contributes to liver fibrosis and has significant implications for new diagnosis and treatment of liver diseases.—Wan, L., Xia, T., Du, Y., Liu, J., Xie, Y., Zhang, Y., Guan, F., Wu, J., Wang, X., Shi, C. Exosomes from activated hepatic stellate cells contain GLUT1 and PKM2: a role for exosomes in metabolic switch of liver nonparenchymal cells. FASEB J. 33, 8530–8542 (2019). www.fasebj.org